The goat meat sector in an Algerian mountain region: analysis of its value chain - Mouhous A.; Kadi S.A.; Guermah H.; Djellal F. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The aim of this study is to determine the different various actors in the goat meat value chain in the mountainous region of Tizi-Ouzou. The study of sixteen goat farms from a prior survey of 80 goat farms, showed that these farms are still conducted in extensive. The goat breeding has evolved and passed from self-consumption to a production for the market. Young goats are the most sold for their tender meat. The marketing of goat meat goes through few intermediaries (actors) that structure the market. Restaurants are a new segment that integrates the value chain and ensures a better value of goat meat. The price of this meat follows that of the sheep meat. Its fluctuation follows the moments of strong demands like the Aid-Al-adha. The demand for goat meat continues to grow. Because of its dietary characteristics, goat meat is beginning to interest a growing consumer segment. For that purpose, a better knowledge of the value chain of this meat will make it possible to target the opportunities for a better structuring of the market and its development.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)